Assessing Scavenger Activity at Delmarva Broiler Farm Composters - Moyle , J.R.; Brooks, L.A.; McCrea, B.A. (International Journal of Poultry Science, 2020)
Background and Objective: A major component of biosecurity on commercial broiler farms is limiting movement of individuals, animals, or other fomites between farms. Scavengers, particularly vultures and other animals, can travel back and forth between farms, carrying diseases and parasites with them as they search for food such as poultry mortalities. Of particular concern are the avian scavengers, Turkey Vultures (Cathartes aura) and Black Vultures (Coragyps atratus), because of their ability to travel long distances and visit multiple farms in a single day. As a result of farmer concern regarding increases in avian scavengers, this study was conducted to assess activity at commercial poultry operations. Materials and Methods: This was an observational study based on 318 days of viewing on four farms. Game cameras were placed on four commercial broiler farms pointed at the composters and farmer surveys were filled out on several other farms. Results: Based on 318 days’ worth of data, Turkey Vultures were seen on 59% (n = 187) of the days and Black Vultures were seen on 14% (n = 44) of the days. On 28% (n = 89) of the camera days, the species of vulture could not be distinguished and for 21% (n = 66) of the days, no vultures were present at the broiler farm composter. The largest groups of vultures were seen in the morning and then again, less frequently, in the afternoon hours. Conclusion: Based on the farmer scouting results, the majority of the time (27.7% of instances), vultures were seen on the manure structure, which was often located near the composter. Other animals seen while using the game cameras included cats, eagles, hawks, dogs, raccoons and foxes.